Cost-effective multi-objective optimal positioning of magnetorheological dampers and active actuators in large nonlinear structures. (January 2017) - Askari, Mohsen; Li, Jianchun; Samali, Bijan
The optimal number and location of control devices not only play a major role in an effective structural control system but also lead to a cost-effective design. This article presents a multi-objective optimization method based on a new genetic algorithm for simultaneous finding of the optimal number and placement of actuators and magnetorheological dampers, in active and semi-active vibration control of structures. The proposed strategy considers three objective functions to be minimized through optimization, including peak inter-storey drift ratio, peak acceleration and peak base shear force to make sure both human comfort and safety of the structure are guaranteed. Also, by choosing a pre-defined level of performance on dynamic responses of a structure, the designer can decide on decreasing or increasing the number of control devices in a systematic way and minimize the control cost. The approach is then validated through a nonlinear 20-storey benchmark problem. The results from active control system show how a problem that was initially solved with 25 actuators can be solved with less than a quarter of those actuators, having similar results in terms of aforementioned indices. The optimal distribution of different numbers of magnetorheological dampers in the same benchmark building is also studied in this article and compared to those obtained from actuators. Due to highly nonlinear behaviour of these devices, and also the complexity of the under-study benchmark structure, few reported researches have been conducted in this area. Also, the comparison between optimal places of active and semi-active control devices in the same structure has hitherto not been reported in the open literature.